PENGARUH PENGGUNAAN MODEL PEMBELAJARAN CONCEPTUAL UNDERSTANDING PROCEDURES BERBANTUAN GEOGEBRA TERHADAP KEMAMPUAN REPRESENTASI MATEMATIS - Aisyah Dwia Ningsih; Syahriani Sirait (MES: Journal of Mathematics Education and Science, 2026)
This study aims to determine the effect the Concepual Understanding Procedures learning model on student’s mathematical representation abilities. This research was conducted at MTs S Nurul Iman Simpang Empat in the 2025/2026 academy year. The type of research used was a quasi experimental design with a two group pretest-posttest design. The population of this study consisted of all eighth grade student’s. The samples were class VIII-B as the experimental class, which was taught using the Concepual Understanding Procedures learning model and class VIII-C as the control class, which was taught using a direct instruction model. After the learning process was completed, the posttest resultes showed that the average score of the experimental class 82.4, while the control class was 76.6. The results of the t-test showed that it can be concluded that there is a significant effect of the Concepual Understanding Procedures learning model on student’s mathematical representation abilities.